2019
DOI: 10.1007/s11307-018-01313-2
|View full text |Cite
|
Sign up to set email alerts
|

PET Imaging of the P2X7 Ion Channel with a Novel Tracer [18F]JNJ-64413739 in a Rat Model of Neuroinflammation

Abstract: Purpose: The P2X7 receptor, an adenosine triphosphate (ATP)-gated purinoreceptor, has emerged as one of the key players in neuroinflammatory processes. Therefore, developing a positron emission tomography (PET) tracer for imaging of P2X7 receptors in vivo presents a promising approach to diagnose, monitor, and study neuroinflammation in a variety of brain disorders. To fulfill the goal of developing a P2X7 PET ligand as a biomarker of neuroinflammation, [ 18 F]JNJ-64413739 has been recently disclosed. Procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
51
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 65 publications
(73 reference statements)
1
51
0
Order By: Relevance
“…Han et al attempted to evaluate [ 11 C]GSK1482160 in vivo in the EAE model but did not succeed due to the low affinity of the tracer for rat P2X 7 R [31]. Systemic and intracerebral LPS models have been used to evaluate the currently available P2X 7 R tracers [17,30,32]; however, these artificial models are not ideal and P2X 7 R overexpression may not reflect the real pathological expression levels in neuroinflammation. We used the acute EAE model in Lewis rats which is characterized by microglia activation and macrophage infiltration mainly in the spinal cord and to a lesser extent in the brain stem and cerebellum [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Han et al attempted to evaluate [ 11 C]GSK1482160 in vivo in the EAE model but did not succeed due to the low affinity of the tracer for rat P2X 7 R [31]. Systemic and intracerebral LPS models have been used to evaluate the currently available P2X 7 R tracers [17,30,32]; however, these artificial models are not ideal and P2X 7 R overexpression may not reflect the real pathological expression levels in neuroinflammation. We used the acute EAE model in Lewis rats which is characterized by microglia activation and macrophage infiltration mainly in the spinal cord and to a lesser extent in the brain stem and cerebellum [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Few PET tracers targeting P2X 7 R have recently been reported that display good affinity and blood brain barrier (BBB) permeability. For instance, Berdyyeva et al evaluated a fluor-18 labeled P2X 7 R antagonist, [ 18 F]JNJ-64413739, in a neuro-inflammatory model using intracerebral lipopolysaccharide (LPS) injection and found an increase of tracer uptake in the LPSinjected part of the brain compared to the contralateral side [17]. The same tracer was also evaluated in nonhuman primates (NHP) and showed target engagement and dose-dependent occupancy in the brain [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the cerebellum was regarded as a preferable reference region of neuroradiological imaging [ 128 , 144 , 145 ]. However, new anatomical [ 26 , 146 ], cell biological and physiological approaches have moved it to a role in multiple functions for the organism and as an emancipated part of the brain.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a collection of further potential PET tracers occurred. The results of a phase 1 study were presented recently by Koole et al [ 125 ] for the triazole derivative [ 18 F] JNJ64413739 ( Figure 11 : [ 48 ]) developed at the Janssen laboratories [ 125 , 126 , 127 , 128 ]. The compound with appropriate log P of 2.05 and selectivity for the target receptor is regarded as a promising structure for further evaluation as a PET tracer.…”
Section: Target Receptors and Ligandsmentioning
confidence: 99%
See 1 more Smart Citation